Compliance with a personalised home exercise programme in chronic low back pain patients after a multidisciplinary programme: A pilot randomised controlled trial - Lenoir dit Caron, R.; Rouzée, M.; Coquart, J.; Gilliaux, M. (Frontiers in Rehabilitation Sciences, 2022)
Background Chronic low back pain (CLBP) is a very common problem throughout the world. One treatment possibility is the multidisciplinary programme (MP) in a rehabilitation centre, which provides intensive rehabilitation through physical exercise to quickly improve the patient conditions. Patients nevertheless do not always continue the exercises when they return home. This study thus evaluated compliance with a personalised home-based programme for CLBP patients post-MP. Methods A randomised controlled single-blind trial was conducted. Thirty patients were randomised into two groups and participated in an MP for 4 weeks. They were then given an exercise booklet for home rehabilitation. In addition, each patient in the experimental group constructed a personalised exercise programme with a physiotherapist. The control group was only encouraged to continue the exercises at home. To assess therapeutic compliance, both groups were asked to document each completed exercise in a logbook. In addition, pain intensity, flexibility, muscle endurance, activity limitations, participation restrictions, and beliefs about physical activity were assessed at the beginning and end of the MP and again after 12 weeks at home. Results Compliance was good for all activities in both groups, but there were no significant differences between groups. All participants improved on the criteria by the end of MP, and both groups maintained the improvements in most of the criteria at 3-month follow-up. Conclusion This study showed the effectiveness of an MP for CLBP in the short and medium term. However, future research should focus on longer-term compliance.